Kinetics of Os(VIII) and Mn(VII) Catalysed Oxidation of Thiocyanate by Periodate in Alkaline Medium - Ramesh, A.; Syama Sundar, B.; Radhakrishna Murti, P.S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of thiocyanate with periodate in presence of permanganate and Os (VIII) as catalysts has been studied. The reactions are found to be zero order in oxidant, first order in MnO4- /Os(VIII), first order in substrate, independent of alkali in MnO4- catalysed reactions, while it is of fractional order in alkali in Os(VIII) catalysed reactions. Os(VIII) is more effective as catalyst than Mn04 under catalytic conditions. Suitable mechanisms have been postulated to explain the kinetics observed in both the cases.